Optic Nerve Diffusion Measurement from Diffusion-Weighted Imaging in Optic Neuritis - Hickman, Simon J.; Wheeler-Kingshott, Claudia A. M.; Jones, Stephen J.; Miszkiel, Katherine A.; Barker, Gareth J.; Plant, Gordon T.; Miller, David H. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Increases in apparent diffusion coefficient (ADC) from diffusion-weighted (DW) imaging are thought to be due to axonal disruption, and changes have been well documented in multiple sclerosis lesions. DW imaging of the optic nerves, however, presents many challenges. The goal of this study was to measure ADC in patients with optic neuritis by using zonal oblique multisection echoplanar imaging.METHODS: The optic nerves of eighteen patients who had experienced an attack of optic neuritis 1 year previously and 11 control subjects were imaged with the diffusion sequence (usable data were available from 16 patients and 10 control subjects). The orbital optic nerves were segmented by a blinded observer by using a computer-assisted threshold-based contouring technique, and the mean ADC was determined.RESULTS: The mean ADC from diseased optic nerves was 1324 × 10−6mm2/s, compared with 990 × 10−6mm2/s from healthy contralateral optic nerves (P = .005 versus diseased optic nerves) and 928 × 10−6mm2/s from control optic nerves (P = .006 versus diseased optic nerves and P = .40 versus healthy contralateral optic nerves). The diseased optic nerve ADC correlated with both visual (e.g., rS = 0.73; P = .001 for logMAR visual acuity) and electrophysiological parameters (e.g., rS = −0.57, P = .021 for visual evoked potential central field amplitude [VEP]).CONCLUSION: It has been possible to apply DW imaging in a patient population, and, in the chronic phase following optic neuritis, the correlation of mean ADC with the clinical and electrophysiological parameters suggests that the ADC is giving a surrogate measure of axonal disruption in the chronic, postinflammatory optic nerve lesion.